Analisis Laju Asimilasi Padi Hitam akibat Aplikasi Mikoriza Arbuskula dan Jerami Padi pada Sawah Tadah Hujan - Safriadi; Muliandari, Nadya (Politeknik Negeri Lampung, 2025)
Black rice cultivated on land with low water content can adapt and grow well by utilizing rainfed land. Arbuscular Mycorrhizal Fungi (AMF) application increase water and nutrient absorption. Soil moisture plays role in the development of AMF. Attempt to maintain soil moisture can be balanced by applying rice straw to the land. This research aimed to examine the role of mycorrhiza and rice straw and their interactions independently in increasing the rate of assimilation and relative growth of black rice in rainfed rice fields. The experiment was conducted in Tebas District, Sambas Regency from July to December. This research method used a split-plot design with randomized block design consisted of main plot and subplot. The main plot was AMF treatment (without AMF and AMF administration), and the subplots were rice straw dosage (ton/ha) (0, 5, 10, 15). The experiment was repeated 3 times, 8 treatments and 16 observed plant samples and continued with Honestly Significant Difference (HSD) test with 5% level. Variables of this observation are leaf area, total dry weight, and net assimilation rate. The result showed that the interaction of AMF and rice straw treatment influenced leaf area, total dry weight and net assimilation rate. Keywords: Black Rice, Mycorrhizal, Rice Straw